Enhancing asset management through a better understanding of energy consumption - Griffin, James S.; Thal, Jr., Alfred E.; Leach, Sonia E. (International Journal of Strategic Property Management, 2014)
Asset management is a systems approach to managing an organization's portfolio of real property assets. Although a range of activities exist to help manage these assets, understanding facility energy consumption is a critical component from a life-cycle decision-making perspective. Since energy consumption is a national concern for most countries, this has resulted in various initiatives regarding energy conservation measures. To better understand the factors affecting energy consumption in facilities, energy and meteorological data covering 22 years were collected for 74 sites located throughout the world. A regression model with an adjusted R2 value of 81% was subsequently developed to predict energy consumption for each site. Additionally, using trend analysis, we found that the amount of energy used to meet heating load requirements was much greater than the amount used to meet cooling load requirements. The insight gained through the research can help facility managers develop energy initiatives as part of their overall asset management strategy.First Publish Online: 18 Sep 2014